Functional analysis of DM64, an antimyotoxic protein with immunoglobulin-like structure from Didelphis marsupialis serum - Rocha, Surza Lucia Gonçalves (2002)
Bothrops snake venoms are known to induce local tissue damage such as hemorrhage and myonecrosis. The opossum Didelphis marsupialis is resistant to these snake venoms and has natural venom inhibitors in its plasma. The aim of this work was to clone and study the chemical, physicochemical and biological properties of DM64, an antimyotoxic protein from opossum serum. DM64 is an acidic protein showing 15% glycosylation and with a molecular mass of 63 659 Da when analysed by MALDI-TOF MS. It was cloned and the amino acid sequence was found to be homologous to DM43, a metalloproteinase inhibitor from D. marsupialis serum, and to human α1B-glycoprotein, indicating the presence of five immunoglobulin-like domains. DM64 neutralized both the in vivo myotoxicity and the in vitro cytotoxicity of myotoxins I (mt-I/Asp49) and II (mt-II/Lys49) from Bothrops asper venom. The inhibitor formed noncovalent complexes with both toxins, but did not inhibit the PLA2 activity of mt-I. Accordingly, DM64 did not neutralize the anticoagulant effect of mt-I nor its intracerebroventricular lethality, effects that depend on its enzymatic activity, and which demonstrate the dissociation between the catalytic and toxic activities of this Asp49 myotoxic PLA2. Furthermore, despite its similarity with metalloproteinase inhibitors, DM64 presented no antihemorrhagic activity against Bothrops jararaca or Bothrops asper crude venoms, and did not inhibit the fibrinogenolytic activity of jararhagin or bothrolysin. This is the first report of a myotoxin inhibitor with an immunoglobulin-like structure isolated and characterized from animal blood.